غزہ و اسرائیل تنازع میں جدید ہتھیاروں کے ماحولیاتی اثرات کا تجزیاتی مطالعہ: An Analytical Study of the Environmental Impacts of Modern Weapons in the Gaza-Israel Conflict - Rubab, Sahrish; Dr. Sobia Khan (Al Basirah, 2025)
Arab Israel conflict has a long history, Since the world war first when the British empire started populating Jews from around the word in Palestine, there broke several wars among them, however in term of destruction and human losses the current ongoing war of Gaza-Israel is the deadliest. This paper presents a critical analysis of the recent Gaza-Israel conflict, focusing on the use of modern weaponry and its environmental repercussions. The already available literature has discussed the environmental impact of deadly wars on that war zone. After the Gulf war of 1990 various researchers have discussed the impact of modern weaponry in term of environment pollution. HRW and BT selem has prepared reports about the destructive effects of drone attacks and phosphorus bombardments. The study highlights how the deployment of advanced military technologies, including drone strikes, air raids, and white phosphorus munitions, has caused not only significant human casualties but also widespread ecological damage. Environmental consequences include severe air and water pollution, the destruction of agricultural lands, contamination of natural resources, and a serious threat to regional biodiversity. Furthermore, the lingering effects of chemical residues, war debris, and toxic gases have created long-term health risks for the civilian population and disrupted the local ecosystem. Drawing upon reports from environmental experts, human rights organizations, and international bodies such as the United Nations, this research suggests that Islamic teaching that forbid environmental harm are aligned with Geneva conventions and International laws. The paper underlines the urgent need for global intervention. The paper concludes by recommending sustainable, humanitarian, and ecological measures to mitigate the environmental and human costs of modern warfare in conflict-affected regions.